2022
DOI: 10.1111/are.15777
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Weissella cibaria KY10 derived from digestive tract of healthy shrimp exhibits strong antibacterial effects against Vibrio parahaemolyticus causing AHPND in shrimp

Abstract: The antibacterial activity of Weissella cibaria KY10 derived from digestive tract of healthy shrimp was investigated against Vibrio parahaemolyticus T.11 causing AHPND.In the co-cultivation assay, W. cibaria KY10 completely inhibited the growth of V. parahaemolyticus T.11 at 12 h under aerobic conditions. The antibacterial substances produced by W. cibaria were detected by GC-MS in parallel to the morphological changes of treated Vibrio cells. The major antibacterial components were higher-pKa acids, such as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…Lim et al [101] successfully explored the antimicrobial activity of W. cibaria, CMU, against oral pathogens, possibly due to acid and hydrogen peroxide. Another strain of W. cibaria, KY10, isolated from shrimp gut, was shown to have bactericidal activity against Vibrio parahaemolyticus T.11 through the mechanism of organic acid release [102]. In another study, Dey et al [103] examined the antibacterial activity of W. confusa DD_A7 isolated from kimchi and found that the DD-A7 strains trigger the oxidative stress to inhibit the growth of extended-spectrum β-lactamase (ESBL)-positive E. coli, which are emerging pathogens.…”
Section: Antimicrobial Potentialmentioning
confidence: 99%
“…Lim et al [101] successfully explored the antimicrobial activity of W. cibaria, CMU, against oral pathogens, possibly due to acid and hydrogen peroxide. Another strain of W. cibaria, KY10, isolated from shrimp gut, was shown to have bactericidal activity against Vibrio parahaemolyticus T.11 through the mechanism of organic acid release [102]. In another study, Dey et al [103] examined the antibacterial activity of W. confusa DD_A7 isolated from kimchi and found that the DD-A7 strains trigger the oxidative stress to inhibit the growth of extended-spectrum β-lactamase (ESBL)-positive E. coli, which are emerging pathogens.…”
Section: Antimicrobial Potentialmentioning
confidence: 99%